EVALUATION OF CASSAVA (MANIHOT ESCULENTA CRANTZ) ROOT PRODUCTS AS REPLACEMENT FOR MAIZE (ZEA MAYS LINN) IN PULLET AND LAYER PRODUCTION (2012)
Availability of dietary energy is a major problem in poultry in Nigeria. Maize, a conventional energy ingredient is expensive. Cassava, which could be a cheaper alternative energy source, has not been tried in Nigeria. The performance of pullets and layers fed various Cassava Root Products (CRP) was examined in this study. The study was divided into two phases. In the first phase, 408 pullet chicks, 240 growing pullets and 240 layers were each allotted to eight diets. In diets 1, 2, 3, and 4, maize was replaced with 0%, 25%, 50% and 100% of Unpeeled Cassava Chips (UCC). Diet 5 contained 25% Peeled Cassava Chips (PCC), while diets 6, 7, and 8 had 25%, 50% and 100% replacement with Unpeeled Cassava Pellets (UCP). In phase two, UCC, UCP were compared with Unpeeled Cassava Grits (UCG) which replaced maize at 50% and 100% in the diets of 210 chicks, 210 growers and 315 layers. The Control Diet (CD) contained 100% maize. All experiments were in a completely randomized design with three replicates of 17, 10, 10, 10, 10 and 15 birds per replicate, respectively. Parameters measured for all the birds included Feed Intake (FI), Weight Gain (WG), Feed Conversion Ratio (FCR) and mortality. Age at First Egg (AFE) and Hen Day Production (HDP) were also recorded for growers and layers, respectively. Feacal and blood samples were collected for nutrient digestibility and serum thiocyanate determination. Data obtained were analysed using descriptive statistics and ANOVA (P=0.05). Birds fed 25% CRP were not significantly different from those on CD for all the parameters. The WG of chicks fed 50% and 100% UCC and 100% UCP were significantly lower than those fed CD. Average FCR of 50% CRP was similar to those on CD. There were no significant difference between growers fed CRP and CD for WG (8.4 g/day - 10.0 g/day), FCR (8.0 - 9.4) and mortality (0.0-3.6%). Average FI, HDP and WG of layers fed 100% UCP were significantly lower than those on CD. Average FI, WG, and FCR of chicks fed 100% UCG (31.2 g/day, 10.7 g/day and 2.9 respectively) were similar to those on CD (30.9 g/day, 10.7 g/day and 2.9, respectively). Performances of growers fed UCG were not significantly different from that of CD, while AFE of growers fed 100% UCC (153 days), and 100% UCP (154 days) were higher than those on CD (146 days). Average HDP of layers fed 100% chips (57.8%), pellets (58.6%) and grits (58.3%) were significantly lower than those on CD (63.1%). Feed intake and WG for layers on 100% UCG were similar to those recorded for the CD. Nutrient digestibilities of growers were similar. Nitrogen retention of chicks and layers fed 100% CRP were lower than those on CD. Serum thiocyanate values of layers fed 50% CRP were higher than CD and lower than 100% UCC, UCP and UCG. Complete replacement of dietary maize with cassava chips, pellets and grits resulted in optimum performance for growers while 50% replacement achieved same for chicks and layers.